Taste Alteration in Patients Receiving Chemotherapy - Elif Sözeri; Sevinç Kutlutürkan (European Journal of Breast Health, 2015)

(untitled)
Objective:This study is aimed to determine factors that affect conditions of patients receiving chemotherapy in terms of experienced taste alteration.Materials and Methods:In this descriptive study, 184 patients receiving chemotherapy were included in the sample. Data were collected during the period of December 2013 to May 2014 using “Patient Characteristics Identification Form” and “Chemotherapy-induced Taste Alteration Scale (CiTAS).” The data were analyzed using SPSS 20 (SPSS Inc., Chicago IL, USA) statistical software in terms of number, percentage, Mann-Whitney U test, and Kruskal-Wallis H test.Results:The mean age of the patients was 55.5±11.8 and 57.1% of them were female. The clinical diagnosis of the patients were most frequently breast cancer (n=46), colorectal cancer (n=45), and lung cancer (n=25). Furthermore, 37.5% of the patients were in clinical stage II; 15.8% of the patients received paclitaxel+herceptin and 14.1% received gemcitabine+cisplatin chemotherapy protocols. Data demonstrated significant differences in mean scores (p<0.05) taken from “Decline in Basic Taste” and “Phantogeusia and Parageusia” subscales with patients with or without xerostomia. There were significant differences in the average scores of the subscales between those with and without a sore mouth “Discomfort” and “General taste alterations” (p<0.05).Conclusion:It has been established that patients receiving chemotherapy experience substantial alteration in taste by exposure of different subscales of CiTAS. Analysis of scores collected from different subscales of CiTAS with respect to sociodemographic and pathological differences showed that patients with xerostomia and sore mouth experienced more severe taste alterations.